Study of reading habits 1987 - Värmland - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Värmland. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys, such as the opinion on how the respondent´s local morning paper cover different sports, the opinion on the length of the news articles and the importance of colour pictures in the morning paper. Respondents had to indicate what kind of news they would read first, good ones or bad ones. The respondent also had to compare the two local papers Nya Wermlands-Tidningen and Värmlands Folkblad with regard to a number of qualities. Furthermore the respondents had to indicate on a scale how interested they were in a number of activities.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Värmland. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys, such as the opinion on how the respondent´s local morning paper cover different sports, the opinion on the length of the news articles and the importance of colour pictures in the morning paper. Respondents had to indicate what kind of news they would read first, good ones or bad ones. The respondent also had to compare the two local papers Nya Wermlands-Tidningen and Värmlands Folkblad with regard to a number of qualities. Furthermore the respondents had to indicate on a scale how interested they were in a number of activities.
Läsvanestudien 1987 - Värmland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap